VD_FINDINFO HC / 2011 / 280 vom 21. März 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, HEURES DE TRAVAIL SUPPLÉMENTAIRES | 343 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 465 al. 1 CPC, 46 al. 1 LJT, 46 al. 2 LJT, 405 al. 1 CPC (CH)